3-Acetyl-5-methyl-1-(4-methylphenyl)-1H-pyrazole-4-carboxamide - Abdel-Aziz, H.A.; Bari, A.; Ng, S.W. (International Union of Crystallography, 2010)
In the title compound, C14H15N3O2, the phenylene ring is disordered over two orientations. As a result, the almost planar pyrazole ring (r.m.s. deviation = 0.004 angstrom) forms dihedral angles of 59.8 (1) and -61.9 (1)degrees with the two orientations of the phenylene ring. The dihedral angle between the two orientations is 59.2 (1)degrees. In the crystal, inversion dimers lined by pairs of N-H center dot center dot center dot O hydrogen bonds occur; there is also an intramolecular N-H center dot center dot center dot O bond.